FAKTOR PENYEBAB, DAMPAK DAN STRATEGI PENYELESAIAN KONFLIK ANTAR WARGA DI KECAMATAN WAY PANJI KABUPATEN LAMPUNG SELATAN - Kuniawan, Dedi; Syani, Abdul (JURNAL SOSIOLOGI, 2013)
In living our lives in Indonesia, diversity is a good friend who has always been inherent in ourselves. The difference between the individual and the individual centres is a destiny which requires us to understand each other while living in the community. The existence of differences that caused this keberanekaragaman can give a crack against the onset of a conflict. The presence of such a conflict in this life must give an impact, be it in the form of a positive impact or a negative impact. Avoiding conflict in the life of the community by means of a personal nature in the form of improvements to rehabilitate ethics and increase levels of intellect is the most basic way to create a life that is secure, tranquil, peaceful and dignified manner. Conflicts between residents who fought in the South Lampung Regency Banner Way is an example of conflict arising from differences that exist in the life of society are not faced with the nature and attitude wise, finally creating a split in the form of war that makes life no longer can walk with harmony.Â Keywords: factors cause, impact, conflict resolution strategy